Pneumocystis jirovecii pneumonia associated with immune checkpoint inhibitors: A systematic literature review of published case reports and disproportionality analysis based on the FAERS database - Xia, Shuang; Gong, Hui; Wang, Yi-kun; Liu, Ling; Zhao, Yi-chang; Guo, Lin; Zhang, Bi-kui; Sarangdhar, Mayur; Noguchi, Yoshihiro; Yan, Miao (Frontiers in Pharmacology, 2023)
Background: Pneumocystis jirovecii pneumonia (PJP) has been reported with ICIs but limited to case reports. The clinical features of PJP with ICIs remain mostly unknown. This study aims to investigate the association of PJP with ICIs and describe clinical features. Methods: Reports of PJP recorded in FAERS (January 2004–December 2022) were identified through the preferred term “Pneumocystis jirovecii pneumonia”. Demographic and clinical features were described, and disproportionality signals were assessed through the Reporting Odds Ratio (ROR) and Information Component (IC), using traditional chemotherapy and targeted therapy as comparators, and adjusting signals by excluding contaminant immunosuppressive drugs and pre-existing diseases. A systematic literature review was conducted to describe clinical features of published PJP reports with ICIs. Bradford Hill criteria was adopted for global assessment of the evidence. Results: We identified 677 reports of PJP associated with ICIs, in which 300 (44.3%) PJP cases with fatal outcome. Nivolumab (IC025 2.05), pembrolizumab (IC025 1.88), ipilimumab (IC025 1.43), atezolizumab (IC025 0.36), durvalumab (IC025 1.65), nivolumab plus ipilimumab (IC025 1.59) have significant signals compared to other drugs in FAERS database. After excluding pre-existing diseases and immunosuppressive agents which may increase susceptibility of PJP, the signals for PJP associated with nivolumab, pembrolizumab, durvalumab, nivolumab plus ipilimumab remained robust (IC025 > 0). When compared to other anticancer regimens, although all ICIs showed a lower disproportionate signal for PJP than chemotherapy, nivolumab (IC025 0.33, p < 0.001), pembrolizumab (IC025 0.16, p < 0.001), both PD-1 inhibitors, presented a higher signal for PJP than targeted therapy. Male gender (IC025 0.26, p < 0.001) and age >65 years (IC025 0.38, p < 0.001) were predominant in PJP cases associated with across all ICIs. In literature, 15 PJP cases associated with ICIs were reported in 10 published case reports. 12 of 15 (80.0%) of cases received PD-1 inhibitors before PJP was diagnosed. Conclusion: By the combined analysis of post-marketing data from FAERS and published case reports, we identified ICIs may be associated with PJP, especially in males aged >65years. After accounting for confounders, PD-1 inhibitors emerged with a robust disproportionality signal when compared to PD-L1/CTLA-4 inhibitors as well as targeted therapy. Further research is warranted to validate our findings.